Ultratrace analysis of Antarctic snow and ice samples using high resolution inductively coupled plasma mass spectrometry - Ashley Townsend; Edwards, PR (1998)
High resolution ICP-MS was used to determine the concentrations of Al, Sc, V, Mn, Fe, Co, Pb and Bi in snow and ice from Antarctica. To overcome some potentially problematic spectral interferences, measurements were acquired in both low and medium resolution modes. Small sample volumes were analysed using a microconcentric nebuliser. After rigorous instrument cleaning and sample preparation, detection levels in the low and sub-pg g-1 range (0.3-48 pg g-1) were found for all elements. Concentration values were determined for a continental snow, sea ice snow and a representative ice core. Concentration ranges for all snow samples (n=25) were (in pg g-1): Al (30-2000), V (2-16), Mn (2-30) and Fe (30-1500), while Sc and Co were typically below detection or blank limits. The ice core sample had Al, Mn, Fe and Pb concentrations of 90, 7, 110 and 1 pg g-1, respectively, while Sc, V, Co and Bi could not be quantified (below detection or blank limits). The reliability of the analytical method for Fe was confirmed by flow injection analysis with spectrophotometric detection.